Assessment of the treatment of domestic sewage by a vertical-flow artificial wetland at different operating water levels. (20th January 2019) - Lu, Shibao; Gao, Xuerui; Wu, Pute; Li, Wei; Bai, Xiao; Sun, Miao; Wang, Ai
Abstract: Artificial wetlands are a sewage treatment technology that operate via the optimization of the physical, chemical, and biological effects of wetland natural ecosystems. The operating conditions and treatment efficiencies of artificial wetlands are researched based on the parameters of domestic sewage, while a vertical-flow artificial wetland is used to simulate domestic sewage as the inlet water of artificial wetlands. The results show that the oxygen-nitrogen removal rate is highest when the water level is 3 cm, while the ammonia nitrogen removal rate increases as the height of the operating water level decreases. When the water level exceeds 35 cm, the nitrate-nitrogen removal rate by the artificial wetland is maintained at a high level, while the nitrate-nitrogen removal rate is highest during operation at the full water level. More nitrite accumulates during operation at a low water level. Considering the total nitrogen removal rate, the vertical-flow artificial wetland reactors M1, M2, and M3 achieved better total nitrogen removal efficiencies. When the water level is 35 cm, the total nitrogen removal rate of the three reactors is the highest. Different operating water level heights do not affect the total phosphorus removal. The Chemical Oxygen Demand（COD） removal efficiency of reactors is higher when the operating water level of the artificial wetland is reduced; that is, the four reactors reached the highest COD removal rate during operation at a low water level. Highlights: Vertical-flow artificial wetland is simulated the domestic sewage as inlet water of artificial wetland. Oxygen nitrogen removal rate is the best when water level is 3cm. Ammonia nitrogen removal rate shall rise with the reducing of height of operating water level. Removal effect of pollutant at different water level is quite different.